The Study of Burden of Family Caregivers of Patients Living with Psychiatric Disorders in Remote Area of Nepal - Kunwar, D.; Lamichhane, S.; Pradhan, N.; Shrestha, B.; Khadka, S.; Gautam, K.; Risal, A. (Kathmandu University Medical Journal, 2020)
Background Family caregivers of psychiatric disorders likely to face burden. There is a paucity of data regarding the caregiver burden in psychiatric disorders in context of Nepal.Objective To study the caregiver burden in families with psychiatric illness and to find association between socio-demographic variables and caregiver burden in families with psychiatric illness.Method This is an analytical cross-sectional study. The participants (n=96) were caregiver of patients visiting outpatient department of two government of Nepal primary health care centers namely, Panchkhal Primary Health Care Center (PHC) Kavre District and Barhabise Health Care Center Sindhupalchowk district. The sample size has been determined by using statistical formula. Family burden assessment schedule (FBIS) was used for the study.Result The majority of the caregivers were females 56.3%. Most of the caregivers were aged below 45 years 54.2%. The large number of participants were single or separated 74%. The mean score of family burden assessment schedule was 27 ± 9.8 (range 0 to 48) with positive rate of 59.4%.Among the objective burden domains disruption of family leisure 61.5% was the most frequently reported burden. The subjective burden was reported in 95%. There were significant differential demographic associations with different domains of caregivers’ burden.Conclusion Caregivers of Psychiatric patients experience different kind of burden of care. Our findings highlight the support to the family members to reduce their burden.